KETERAMPILAN 4C SEBAGAI STRATEGI PENGEMBANGAN KOMPETENSI CRITICAL THINKING GEN Z DI ERA REVOLUSI INDUSTRI 4.0 DAN SOCIETY 5.0 - Frida Nurmarliana; Mirna Nur Alia Abdullah (SABANA: Jurnal Sosiologi, Antropologi, dan Budaya Nusantara, 2024)
In the era of Industrial Revolution 4.0 and Society 5.0, 4C skills (communication, collaboration, creaticity, and critical thinking) have a major role in the development of Generation Z competencies in the era of Industrial Revolution 4.0 adn Societ 5.0. However, among the four skills, critical thinking skills have the most significant role in helping Generation Z deal with complexity and rapid change. Rapidly evolving technology and social changes also require Generation Z to think critically, as it helps in understanding and navigating information as well as challenges and making the right descisions in diverse situasions. Critical thinking skills also play an inmortant role in helping Generation Z develop a healthy skepticism towards information in the digital world. This article aims to explore the role og critical thinking skills as an important strategy in the development of Generation Z competencies. The methodology involves analyzing current literature in the fields of education, sociologi, and psychology to analyze the challenges and strategies associated with developing critical thinking among Generation Z. It is hoped that this article will provide a better understanding of the importance of critical thinking skills in the context of Generation Z.